Post-truth and echo chamber phenomena in the facebook of Jokowi and Prabowo - Syahrur Marta Dwisusilo, Moh. Gandhi Amanullah, (Opción, 2019)
This study aims at investigating how far the post-truth and echo chamber phenomena penetrate into Indonesian social media via comparative qualitative research methods. The data were taken from the messages related to the political contestation of Jokowi and Prabowo’s supporters on Facebook. The results show that Indonesian social media has been penetrated by the post-truth and echo chamber phenomena. In conclusion, when the sample was taken from the group with the highest number of members, it is known that there are many posts with the topics of propaganda, criticism, hate speech, mockery, logical fallacy, and fake information in it